Fenologia, crescimento e produção de Lippia insignis Moldenke (Verbenaceae) nas condições climáticas de Feira de Santana, Bahia - Gonzaga, Mariluci Lopes (2025)
Brazil is considered one of the most biodiverse countries in the world, and among its biomes, the Caatinga stands out, harboring numerous plant species, many of them native. The genus Lippia comprises approximately 200 species and is widely used in traditional medicine, with significant potential for the pharmaceutical industry. However, some of these species are classified as vulnerable, such as Lippia insignis Moldenke, a shrub native to the rocky fields of the Chapada Diamantina, Bahia, with medicinal and insecticidal potential. This underscores the need for studies, particularly in the areas of conservation and cultivation, to support the sustainable use of this species. Thus, this study evaluated the effect of seasonality on the phenology, growth, and production of L. insignis under the climatic conditions of Feira de Santana, Bahia. The study was carried out at the Experimental Unit of the Forest Garden of the State University of Feira de Santana. The species was propagated from mother plants belonging to the Medicinal and Aromatic Plant Collection of the Forest Garden and cultivated under field conditions. Phenological data were collected, as well as growth parameters—plant height, stem and canopy diameter, dry mass of leaves, flowers, stems, and total dry mass, along with total leaf area and essential oil yield. Climatic data were obtained from the National Institute of Meteorology and based on the geographical coordinates provided by the Astronomical Applications Department of the U.S. Naval Observatory. The species exhibited high synchrony in the phenological events of senescence, mature leaves, and sprouting. Fruiting and flowering followed seasonal patterns. Senescence decreased with increasing precipitation, whereas longer photoperiods resulted in greater leaf abscission. Plant height and stem diameter increased under longer day lengths, while total leaf area decreased; canopy diameter increased with higher radiation levels; leaf dry mass increased with higher humidity; and total dry mass and oil yield increased with greater precipitation. These findings demonstrate the influence of climatic factors on the growth of Lippia insignis and contribute to the development of proper management practices, optimizing cultivation and promoting the sustainable use of the species.